2021
DOI: 10.5114/hm.2021.103293
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of different resistance training loads on repeated sprint ability in water polo players

Abstract: Purpose. combining resistance and in-water training is a common practice in water polo. The purpose of this study was to examine the acute effects of different external loads during resistance training on the repeated sprint ability in water polo players. Methods. A total of 9 national level water polo players (age: 21.5 ± 2.0 years) executed, on different occasions, a repeated sprint swimming test (8 × 25 m with a 30-s rest) following a low load (50% of 1-repetition maximum) or a high load (80% of 1-repetitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Moreover, the training level of swimmers that were included in the narrative review was classified according to previously suggested criteria [29] and is presented in Table 2. Competing Level [11] Highly-Trained ≥3 6 National [30] Highlytrained ≥6 ≥6 National [7] Highlytrained --National [8] Highly-Trained --National [32] Highlytrained ≥5 ≥6 National [33] Elite/ international ≥5 ≥6 National/ International [4] Elite/ international ≥2 ≥6 National/ International [31] Highlytrained ≥2 ≥5 National ≥: greater or equal, -: undefined, RT: dry-land resistance training. Elite/ international ≥5 ≥6 National/ International [4] Elite/ international ≥2 ≥6 National/ International [31] Highlytrained ≥2 ≥5 National ≥: greater or equal, -: undefined, RT: dry-land resistance training.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the training level of swimmers that were included in the narrative review was classified according to previously suggested criteria [29] and is presented in Table 2. Competing Level [11] Highly-Trained ≥3 6 National [30] Highlytrained ≥6 ≥6 National [7] Highlytrained --National [8] Highly-Trained --National [32] Highlytrained ≥5 ≥6 National [33] Elite/ international ≥5 ≥6 National/ International [4] Elite/ international ≥2 ≥6 National/ International [31] Highlytrained ≥2 ≥5 National ≥: greater or equal, -: undefined, RT: dry-land resistance training. Elite/ international ≥5 ≥6 National/ International [4] Elite/ international ≥2 ≥6 National/ International [31] Highlytrained ≥2 ≥5 National ≥: greater or equal, -: undefined, RT: dry-land resistance training.…”
Section: Methodsmentioning
confidence: 99%
“…To date, no study has examined the SWIM-RT order. In particular, these studies have used a repeated measures design and applied a counterbalanced [ 11 ] or randomized testing order [ 30 ]. Moreover, maximum strength (high loads) or muscular endurance (low loads) RT sessions were applied before a SWIM session that consisted of different training modes such as endurance [ 11 ] or repeated sprints [ 30 ].…”
Section: Concurrent Resistance and Swimming Training: Acute Physiolog...mentioning
confidence: 99%
See 3 more Smart Citations